ANALISIS HIDROKUINON DAN NIASINAMID PADA KRIM PEMUTIH WAJAH MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI (KCKT ) - Wachyuni Putri Nuraini; Almawati Situmorang; Supandi (Prosiding Seminar Nasional Berseri, 2020)
Hydroquinone is an active substance that can control dark brownish skin pigmentation. Niacinamide is one of the B vitamins that can be used to treat facial skin disorders. This study aims to determine the levels of hydroquinone and niacinamide, is it in accordance with the decision of the Food and Drug Supervisory Agency using the High-Performance Liquid Chromatography (HPLC) method. The chromatographic system used in this method is the C18 column separation column (150 x 4,6 mm), flow velocity 0,75 ml/min, acetonitrile: water (15:85) and wavelength 225 nm. The results obtained the LOD value of hydroquinone is 0,9688 g/L; LOQ value of hydroquinone is 3,2296 g/L; LOD of niacinamide is 1,3185 g/L; LOQ of niacinamide is 4,3952 g/L; accuracy values of hydroquinone and niacinamide in the range 94-105%, while hydroquinone levels 1,9748%, niacinamide levels 214,860 g. The conclusion of the results in this study is in accordance with BPOM’s decision that the hydroquinone levels are not more than 2%, while niacinamide levels are not more than 250 mg.